2017
DOI: 10.1038/s41598-017-07672-0
|View full text |Cite
|
Sign up to set email alerts
|

Human adipose-derived mesenchymal stem cells seeded into a collagen-hydroxyapatite scaffold promote bone augmentation after implantation in the mouse

Abstract: Traumatic injury or surgical excision of diseased bone tissue usually require the reconstruction of large bone defects unable to heal spontaneously, especially in older individuals. This is a big challenge requiring the development of biomaterials mimicking the bone structure and capable of inducing the right commitment of cells seeded within the scaffold. In particular, given their properties and large availability, the human adipose-derived stem cells are considered as the better candidate for autologous cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 42 publications
4
39
0
Order By: Relevance
“…In fact, previous studies [2,13,35] and the present work demonstrated that this kind of scaffold was bioactive, biodegradable, biocompatible, and easily recognized by cells, thanks to the high hydrophilicity and porosity, particularly in terms of macropores, which fostered cell adhesion, colonization, proliferation, and RANKL cytokine production, in agreement with reports in literature referring to different contexts [36,37]. Moreover, once implanted subcutaneously in mice, these scaffolds were extensively vascularized; in line with other findings [38,39], this should have favored graft-host interaction and MSCs survival, and supported the systemic distribution of soluble factors, likely comprising also RANKL, produced by the implanted cells.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, previous studies [2,13,35] and the present work demonstrated that this kind of scaffold was bioactive, biodegradable, biocompatible, and easily recognized by cells, thanks to the high hydrophilicity and porosity, particularly in terms of macropores, which fostered cell adhesion, colonization, proliferation, and RANKL cytokine production, in agreement with reports in literature referring to different contexts [36,37]. Moreover, once implanted subcutaneously in mice, these scaffolds were extensively vascularized; in line with other findings [38,39], this should have favored graft-host interaction and MSCs survival, and supported the systemic distribution of soluble factors, likely comprising also RANKL, produced by the implanted cells.…”
Section: Discussionsupporting
confidence: 93%
“…All efforts were made to minimize the number of animals used and their suffering. Pre- and post-grafting procedures were performed as explained previously (Calabrese et al, 2016b , 2017b ). Briefly, surgical procedures were performed under aseptic conditions, with the animals under gas anesthesia (isoflurane).…”
Section: Methodsmentioning
confidence: 99%
“…Calabrese et al in their studies tested a composite bi-layer type-1 collagen-HA/Mg scaffold for osteochondral regeneration, both in vitro and in vivo. They showed that the combination of this scaffold with mesenchymal stem cells (MSC) derived from adipose tissue (hAD-SCs) in the presence of specific differentiation conditions induce osteochondro differentiation both in vitro and in vivo [19][20][21][22][23].…”
Section: Ceramicsmentioning
confidence: 99%
“…Also, our group tested in vitro and in vivo potential of collagen type-1/Ha-Mg combination to promote bone injury healing. We demonstrated that although biomimetic scaffolds are "per sĂš" able to promote tissue regeneration thanks to their high osteoinductivity, their combination with progenitor cells and growth factors would be more efficient [19][20][21]. Generally, osteogenic cells such as adult stem cells (ASC) isolated from adult tissues like bone marrow, adipose tissue, or muscle are good candidate to be transplanted in skeletal lesion together with an appropriate scaffold.…”
Section: Biomaterials For Bone Tissue Engineering: Current Applicatiomentioning
confidence: 99%